2022
DOI: 10.1111/cen.14737
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical factors related to antibody‐mediated immune response to the subfornical organ

Abstract: Objective We recently reported cases of adipsic hypernatremia caused by autoantibodies against the subfornical organ in patients with hypothalamic‐pituitary lesions. This study aimed to clarify the clinical features of newly identified patients with adipsic hypernatremia whose sera displayed immunoreactivity to the mouse subfornical organ. Design Observational cohort study of patients diagnosed with adipsic hypernatremia in Japan, United States, and Europe. Methods The study included 22 patients with adipsic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Hyperhidrosis, cold limbs, and mild dehydration may occur [1,2]. In addition to an increase in serum Na levels and serum osmolality, an increase in prolactin levels, an increase in the frequency of hypothalamic disorders, and an increase in retroperitoneal tumors have been reported [28]. Moreover, our study revealed that plasma renin activity was significantly higher in the anti-Nax antibody-positive cases.…”
Section: Clinical Symptoms and Complicationssupporting
confidence: 54%
See 4 more Smart Citations
“…Hyperhidrosis, cold limbs, and mild dehydration may occur [1,2]. In addition to an increase in serum Na levels and serum osmolality, an increase in prolactin levels, an increase in the frequency of hypothalamic disorders, and an increase in retroperitoneal tumors have been reported [28]. Moreover, our study revealed that plasma renin activity was significantly higher in the anti-Nax antibody-positive cases.…”
Section: Clinical Symptoms and Complicationssupporting
confidence: 54%
“…Interestingly, recent reports have identified antibodies to SFO and Na x antibodies in patients with clinically diagnosed autoimmune hypernatremia and ROHHAD syndrome. From this, it is possible that some patients in both disease groups develop the disease by a common autoimmune mechanism (Figure 1) [28]. There have been some recent reports supporting the autoimmune mechanism in RO-HHAD syndrome.…”
Section: Findings On the Similar Pathogenic Mechanism In The Two Dise...mentioning
confidence: 92%
See 3 more Smart Citations